The Effect of Rehabilitation Exercises Accompanied by The Shock Wave Device on The Strength of Some Muscles and Chronic Lower Back Pain for Weightlifters - Ghalib, Ahmed Ali; Raheem, Majid Mohammed Ameen (Pubmedia Jurnal Pendidikan Olahraga, 2024)
Athletes who engage in sports that demand the use of great force to overcome great resistance—like weightlifters—are subjected to various loads during training that place stress on their bodies, particularly the musculoskeletal system. As a result, it is common for these athletes to experience lower back pain. One of the most common consequences of spinal injuries that needs to be treated is chronic lower back pain. Natural therapeutic approaches are among the significant and secure approaches that the world has recently started to focus on with great strides, as contemporary methods and techniques have been applied, Physical therapy facilities have used a wide range of treatment techniques, but take caution Shockwave electrophoresis using the shockwave apparatus is an effective method that targets enhancing the muscles' capacity to resume their original function. The purpose of the research was to develop rehabilitation workouts that would work with the shock wave strength gadget. For weightlifters, some lower back stiffness and muscular soreness over time. Find out how exercise affects Treatment for persistent lower back pain with the shock wave gadget enhances muscular strength. For those who exercise weights in between pre- and post-tests. Using a single experimental group design, the researcher used the experimental technique to identify the research community. The Karbala Governorate is home to weightlifting athletes, five of them are wounded.